EFEKTIFITAS PROGRAM PENGASUHAN DALAM MEMENUHI KEBUTUHAN DASAR ANAK BALITA DI UPTD PELAYANAN SOSIAL ANAK BALITA MEDAN - Rina br Manik; Hairani Siregar (Jurnal Intervensi Sosial dan Pembangunan, 2026)
This research is motivated by the importance of parenting in supporting children's growth and development, particularly in physical, emotional, and cognitive aspects. This study employs a qualitative method with a descriptive approach, using direct observation, in-depth interviews, and documentation as data collection techniques. The research subjects consist of five key informants: the head supervisor, the head of the parenting section, a social service analyst, a social worker, and parents of toddlers. Meanwhile, the research object is the effectiveness of the parenting program in meeting the basic needs of the children under care. The results indicate that the care program at UPTD has been fairly effective. Program understanding and target accuracy were well-implemented through training and multidisciplinary assessments. However, implementation was not entirely optimal in terms of timeliness and goal achievement due to limited caregiving staff and insufficient educational facilities. Nevertheless, the program produced tangible positive changes, such as improved nutritional status, emotional stability, social skills, and child independence. Thus, this study affirms that the care program at the UPTD Social Service for Toddlers in Medan has been effective, although improvements in human resources and educational support facilities are still needed to enhance its overall impact.Keywords:  Caregiving Program, Basic Needs of Toddlers, Effectiveness, UPTD Child Social Service